2017
DOI: 10.1111/aab.12352
|View full text |Cite
|
Sign up to set email alerts
|

Effect of five fungicides with different modes of action on cobweb disease (Cladobotryum mycophilum) and mushroom yield

Abstract: The fungicides chlorothalonil, metrafenone, prochloraz-Mn, thiabendazole and thiophanate-methyl were tested in vitro and in vivo for their effect on Cladobotryum mycophilum, the mycoparasite that causes cobweb disease in white button mushroom. In vitro experiments showed that metrafenone (EC 50 = 0.025 mg L −1 ) and prochloraz-Mn (EC 50 = 0.045 mg L −1 ) were the most effective fungicides for inhibiting the mycelial growth of C. mycophilum. Selectivity indexes of the tested fungicides on both C. mycophilum and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 25 publications
2
21
0
Order By: Relevance
“…The T. vulgaris (IEO3B, IEO3A) and S. montana (IEO1A) EOs treatments, at 1% concentration, were as effective as those involving metrafenone. Until now, the most effective treatment for controlling cobweb disease has been with metrafenone [13]. These results agree with those of previous studies carried out in mushroom growing rooms, which showed that the preventative use of T. vulgaris oil was able to control the development of wet bubble disease caused by Mycogone perniciosa in mushrooms with no detrimental effect on the growth of A. bisporus, and provided an overall yield similar to that following the application of a commercial fungicide [20].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The T. vulgaris (IEO3B, IEO3A) and S. montana (IEO1A) EOs treatments, at 1% concentration, were as effective as those involving metrafenone. Until now, the most effective treatment for controlling cobweb disease has been with metrafenone [13]. These results agree with those of previous studies carried out in mushroom growing rooms, which showed that the preventative use of T. vulgaris oil was able to control the development of wet bubble disease caused by Mycogone perniciosa in mushrooms with no detrimental effect on the growth of A. bisporus, and provided an overall yield similar to that following the application of a commercial fungicide [20].…”
Section: Discussionsupporting
confidence: 86%
“…These values (lower than 0.1) are better than those obtained in previous studies with the fungicides chlorothalonil and thiophanate-methyl (SI = 0.38 and 0.21, respectively). However, the fungicides metrafenone, prochloraz-Mn, and thiabendazole showed better selectivity than the EOs tested (SI = 0.00001, 0.0031, and 0.01, respectively) [13]. On the other hand, L. x intermedia and T. mastichina EOs had the greatest inhibitory effect against the A. bisporus mycelium, and their selectivity indexes were the highest ( Table 3).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The control of mushroom pests and diseases therefore currently relies on the application of integrated management programs in addition to the use of chemical pesticides, mostly fungicides . However, an increasing demand for organic products and reports of the emergence of resistant strains (Carrasco et al, 2017) support the case for the development of novel sustainable strategies for mushroom crop protection. In order to reduce fungicide dependence, environmentally friendly biomolecules such as aromatic plant extracts have been tested.…”
Section: Biocontrol Agents For Control Of Mushroom Parasitesmentioning
confidence: 99%